Metodološke rešitve posameznih logističnih procesov v pristanišču - Murtič, Sašo (Perfectus AC, 2020)
Logistics is a part of the service activity, which is related to the supply of raw materials, transport, warehouse and organization of many tasks and jobs, which enable achieving necessary financial effects to industry's manufacturing companies and physical/legal persons through their work processes. The transport is integral part of logistics - it is an individual process which through the integration of all individual logistics processes enables that goods are delivered from point A to point B in time, by strictly specified route. It is often related to forms of organisation, preparation and performance. Due to all these processes it is also related to many factors which can affect an individual procedure in the organisation of transport and other activities which are just smaller parts of the transport. Many factors (integration between organisations, time and space of the individual transport forms and ensuring the security) depend to the form of organisation. The organisation can be unimodal/conventional or multimodal/combined, where many organisations are presented. The performance is bonded to procedures and forms of loading, reloading etc. All these processes should not take up too much time and space in the ports. The subjects of our research are urgent logistics systems, which enable faster management with goods from ship to the truck or wagon. Nowadays, a global market is an open market of goods - metals, minerals, liquids, gases or granulates, which are offered by providers in different forms. Granulates for example are nowadays getting more and more used because of the transport needs - it enables bigger amounts and faster transportation of goods. Those granulates for example, present raw materials for production of glass and metal. Researches have shown that this system is good for transport and a sender, but on the other hand it causes many problems in the ports. Because of the wind impact, the dust powder causes a big loss of goods quantity - and workers, employed in the ports are responsible for that. There are appearing demands for logistics and technological researches, which would give us answers how to shift those goods faster and "throw" not to cause its losses. We were thinking about controlled system of blowing from the ship into the closed crates or even reservoir. We were studying existing systems in the ports and developing the theory, which would "throw" us into the research or into the preparation of the system, which would enable us a new service.
Keywords: logistics processes; logistics systems; logistični procesi; logistični sistemi; management; menedžment; metode dela; working methods